(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Type 2 diabetes mellitus (T2DM) is one of the most common endocrine pathologies characterized by insulin resistance and relative insulin deficiency. In the absence of adequate control, the disease leads to the development of chronic complications affecting the cardiovascular, nervous, renal and visual systems. This review article discusses the main mechanisms of pathogenesis of chronic complications of T2DM and modern approaches to their correction.